PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI STRUKTUR DAN FUNGSI TUMBUHAN - Sholikah, Ta'imul; Indayati, Tatik (Al Tadib : Jurnal Ilmu Pendidikan, 2023)
This research was conducted to determine the effect of the discovery learning model in improving student learning outcomes in the material structure and function of plants. This type of research is a quasi-experimental study using the Cluster Random Sampling technique. The prerequisite test stage uses normality and homogeneity tests. Data analysis used the Independent Sample T test. This calculation is assisted using the SPSS application. The results of the analysis of the data obtained are that the significance value (2-tailed) is 0.00 which is less than 0.05, Ho is rejected and Ha is accepted. So there is the influence of discovery learning in improving student learning outcomes in the material structure and function of plants.